Ethnomedical Survey of Herbs for the Management of Malaria in Karnataka, India - Prakash, Bangalore Nagendrappa; Payyappallimanaa, Unnukrishnan (Ethnobotany Research and Applications, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Herbs used by traditional healers for malaria management were documented in the Tumkur district of Karnataka, India. In total, 31 species of plants in 20 families were used. 30% of the herbal remedies contained species in only three plant families; Fabaceae, Piperaceae, and Zingiberaceae. Leaves were the most commonly used plant part (29%). Eight plant species used in the study area, were documented for the first time for their use in the treatment of malaria. Ethnomedical and antiplasmodial activity of documented species was assessed by comparison with published literature. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>